2004
DOI: 10.1161/01.cir.0000148371.53174.05
|View full text |Cite
|
Sign up to set email alerts
|

Nonuniform Strut Distribution Correlates With More Neointimal Hyperplasia After Sirolimus-Eluting Stent Implantation

Abstract: Background-Little is known about causes of intimal hyperplasia (IH) after sirolimus-eluting stent (SES) implantation.Methods and Results-Intravascular ultrasound was performed in 24 lesions with intra-SES restenosis and a comparison group of 25 nonrestenotic SESs. To assess stent strut distribution, the maximum interstrut angle was measured with a protractor centered on the stent, and the visible struts were counted and normalized for the number of stent cells. In SES restenosis patients, minimum lumen site wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(92 citation statements)
references
References 12 publications
(10 reference statements)
2
84
0
4
Order By: Relevance
“…Another parameter measured is the maximum angle between adjacent stent struts. As reported by Takebayashi et al [9], this measurement correlates with the NIH thickness in IVUS-based studies. NIH thickness was also evaluated looking at the lumen cross-sectional area (L-CSA), the stent cross-sectional area (S-CSA), minimum, maximum, and average distance between the lumen boundary and the stent.…”
Section: Assessment Of Strut Distributionsupporting
confidence: 74%
See 3 more Smart Citations
“…Another parameter measured is the maximum angle between adjacent stent struts. As reported by Takebayashi et al [9], this measurement correlates with the NIH thickness in IVUS-based studies. NIH thickness was also evaluated looking at the lumen cross-sectional area (L-CSA), the stent cross-sectional area (S-CSA), minimum, maximum, and average distance between the lumen boundary and the stent.…”
Section: Assessment Of Strut Distributionsupporting
confidence: 74%
“…A large-scale evaluation of OCT pullback stent analysis will be necessary to further correlate the degree of NIH and circumferential stent strut distribution, as suggested previously by IVUS [9].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…34) In addition, stent fracture is rarely related to very focal intrastent restenosis despite complete abolition of intimal hyperplasia in the remainder of the stented segment. 35) Overall, the published reports have suggested that residual stenosis is a significant component of the restenosis problem, and this indicates that achieving a larger lumen area with adequate stent expansion remains an important strategy for reducing restenosis, even in the DES era.…”
Section: Procedure-and Lesion-related Factorsmentioning
confidence: 99%